2022
DOI: 10.48550/arxiv.2205.02622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverging current fluctuations in critical Kerr resonators

Michael J. Kewming,
Mark T. Mitchison,
Gabriel T. Landi

Abstract: The parametrically pumped Kerr model describes a driven-dissipative nonlinear cavity, whose nonequilibrium phase diagram features both continuous and discontinuous quantum phase transitions. We consider the consequences of these critical phenomena for the fluctuations of the photocurrent obtained via continuous weak measurements on the cavity. Considering both direct photodetection and homodyne detection schemes, we find that the current fluctuations diverge exponentially at the discontinuous phase transition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Indeed, under standard assumptions, critical protocols can achieve the Heisenberg scaling—a quadratic growth of parameter-estimation precision—both with respect to the number of probes and with respect to the measurement time. Furthermore, a recent theoretical work [ 15 ] demonstrated that the optimal limits of precision can be achieved using finite-component phase transitions [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], which are criticalities that take place in quantum optical systems where the thermodynamic limit is replaced by a scaling of the system parameters [ 20 , 29 , 30 , 31 , 32 , 33 , 34 ]. Critical quantum sensors can then also be implemented with controllable small-scale quantum devices, without requiring the control of complex many-body systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, under standard assumptions, critical protocols can achieve the Heisenberg scaling—a quadratic growth of parameter-estimation precision—both with respect to the number of probes and with respect to the measurement time. Furthermore, a recent theoretical work [ 15 ] demonstrated that the optimal limits of precision can be achieved using finite-component phase transitions [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], which are criticalities that take place in quantum optical systems where the thermodynamic limit is replaced by a scaling of the system parameters [ 20 , 29 , 30 , 31 , 32 , 33 , 34 ]. Critical quantum sensors can then also be implemented with controllable small-scale quantum devices, without requiring the control of complex many-body systems.…”
Section: Introductionmentioning
confidence: 99%